Utilization of the Integrated Management of Newborn and Childhood Illness (IMNCI) protocol and associated factors among health care workers in health centers of South Gondar Zone, Northwest Ethiopia: an institution-based mixed study - Belete, Abraham Addis; Agumas, Yeshambel; Tsehay, Asmamaw Ketemaw; Ayele, Habtamu Molla (Frontiers in Health Services, 2024)
Introduction: Globally, 11 million children have died before celebrating their fifth birthday. The introduction of Integrated Management of Newborn and Child Illness protocol reduces under-five morbidity and mortality. However, the share of neonatal mortality is increasing. As a result, the United Nations set sustainable development goals to reduce national neonatal death rates through the utilization of the Integrated Management of Newborn and Child Illness protocol as the main tool for 12 per 1,000 live births by 2030. However, the death rate from preventable causes has increased owing to the low utilization of the protocol.